2020
DOI: 10.1002/2211-5463.12825
|View full text |Cite
|
Sign up to set email alerts
|

Serpin7 controls egg diapause of migratory locust (Locusta migratoria) by regulating polyphenol oxidase

Abstract: Diapause is a state of arrested growth, which allows insects to adapt to diverse environments. Serine protease inhibitors (serpins) play an important role in various physiological processes, including blood coagulation, fibrinolysis, development, complement activation and extracellular matrix remodeling. We hypothesized that serpin may affect energy metabolism and thereby control diapause of migratory locust (Locusta migratoria) embryos by regulating protease cascades. A total of seven nonredundant serpin gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…To better understand the immune mechanisms of L. migratoria manilensis and examine their response to a variety of pathogen challenges, transcriptome sequencing and analysis were performed on migratory locusts. A total amino acid sequences of seven serpin genes ( serpin1 to serpin7 ) were obtained [ 31 ]. Phylogenetic tree analysis showed that Lmserpin1 was similar to serpinB9 , which was involved in the immune response [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the immune mechanisms of L. migratoria manilensis and examine their response to a variety of pathogen challenges, transcriptome sequencing and analysis were performed on migratory locusts. A total amino acid sequences of seven serpin genes ( serpin1 to serpin7 ) were obtained [ 31 ]. Phylogenetic tree analysis showed that Lmserpin1 was similar to serpinB9 , which was involved in the immune response [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serpins carry out various physiological functions in insects, including development, digestion, host-pathogen interactions, and innate immune response. Serpin plays a key role in immune pathways, its involvement in the regulation of the Toll pathway and prophenoloxidase activation is well documented [ 74 ]. Its downregulation was observed in Plutella xylostella after fungal and viral infection, and treatment with mycotoxin [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Serpin plays a key role in immune pathways, its involvement in the regulation of the Toll pathway and prophenoloxidase activation is well documented [ 74 ]. Its downregulation was observed in Plutella xylostella after fungal and viral infection, and treatment with mycotoxin [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Drosophila Spn27A regulates embryonic axis formation by mediating the Toll pathway activity (Hashimoto et al, 2003). In the migratory locust Locusta migratoria , Serpin7 controls embryonic diapause by regulating polyphenol oxidase activity (Chen et al, 2020b). To document the potential TmSPIs that may act in development, their expressions were profiled across life stages including egg, larva, prepupa, pupa, and adult through RNA‐seq data analysis (Figure 5).…”
Section: Resultsmentioning
confidence: 99%